Environmental and morphological constraints interact to drive the evolution of communication signals in frogs. (18th October 2020) - Muñoz, Matías I.; Goutte, Sandra; Ellers, Jacintha; Halfwerk, Wouter
Abstract: Animals show a rich diversity of signals and displays. Among the many selective forces driving the evolution of communication signals, one widely recognized factor is the structure of the environment where animals communicate. In particular, animals communicating by sounds often emit acoustic signals from specific locations, such as high up in the air, from the ground or in the water. The properties of these different display sites may impose different constraints on sound production, and therefore drive signal evolution. Here, we used comparative phylogenetic analyses to assess the relationship between calling site (aquatic versus nonaquatic), body size and call dominant frequency of 160 frog species from the families Ranidae, Leptodactylidae and Hylidae. We found that the frequency of frogs calling from the water was lower than that of species calling outside of the water, a trend that was consistent across the three families studied. Furthermore, phylogenetic path analysis revealed that call site had both direct and indirect effects on call frequency. Indirect effects were mediated by call site influencing male body size, which in turn was negatively associated with call frequency. Our results suggest that properties of display sites can drive signal evolution, most likely not only through morphological constraints imposed on the sound production mechanism, but also through changes in body size, highlighting the relevance of the interplay between morphological adaptation and signal evolution. Changes in display site may therefore have important evolutionary consequences, as it may influence sexual selection processes and ultimately may even promote speciation. Abstract : Frog species that call from the water do it at lower frequencies than nonaquatic frogs. We argue that environmental constraints on body size and vocal sound production interact to drive call frequency evolution in frogs.